Earth : the operators' manual - Alley, Richard B. (W.W. Norton, 2011)
Since the discovery of fire, humans have been energy users. And this is a good thing--our mastery of energy is what separates us from the rest of the animal kingdom and has allowed us to be the dominant species on the planet. However, this mastery comes with a price: we are changing our environment in a profoundly negative way by heating it up. Using one engaging story after another, coupled with accessible scientific facts, world authority Richard B. Alley explores the history of energy use by humans over the centuries, gives a doubt-destroying proof that already-high levels of carbon dioxide are causing damaging global warming, and surveys the alternative energy options that are available to exploit right now. These new energy sources might well be the engines for economic growth in the twenty-first century.--From publisher description.